2018
DOI: 10.3389/fphar.2018.00836
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Mechanism of Action of Diketopiperazines Inhibitors of the Burkholderia cenocepacia Quorum Sensing Synthase CepI: A Site-Directed Mutagenesis Study

Abstract: Quorum sensing (QS) is a bacterial intercellular communication process which controls the production of major virulence factors, such as proteases, siderophores, and toxins, as well as biofilm formation. Since the inhibition of this pathway reduces bacterial virulence, QS is considered a valuable candidate drug target, particularly for the treatment of opportunistic infections, such as those caused by Burkholderia cenocepacia in cystic fibrosis patients. Diketopiperazine inhibitors of the acyl homoserine lacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…S3). This suggests that the Cys residue at position 131 is somehow involved in the binding of BH, despite its location in a region of the enzyme far from the binding site of other CepI inhibitors (39). Using qPCR, we investigated the expression of cepI (BCAM1870) and two QS-regulated genes (aidA [BCAS0293] and zmpA [BCAS0409]) (38) in cultures derived from the TOB-exposed biofilm of lineage 2.…”
Section: Resultsmentioning
confidence: 99%
“…S3). This suggests that the Cys residue at position 131 is somehow involved in the binding of BH, despite its location in a region of the enzyme far from the binding site of other CepI inhibitors (39). Using qPCR, we investigated the expression of cepI (BCAM1870) and two QS-regulated genes (aidA [BCAS0293] and zmpA [BCAS0409]) (38) in cultures derived from the TOB-exposed biofilm of lineage 2.…”
Section: Resultsmentioning
confidence: 99%
“…During the last few years, we focused our attention on this topic, proposing new targets, such as the glutamate racemase (Israyilova et al, 2016), new strategies, such as the inhibition of quorum sensing (Scoffone et al, 2016;Buroni et al, 2018) and new drugs (Scoffone et al, 2014), to fight B. cenocepacia infections. We found that the benzothiadiazole derivative C109 is highly effective against B. cenocepacia (Scoffone et al, 2015) and other Gram-negative and-positive bacteria, including Mycobacterium abscessus (Hogan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The binding site of TofI can be occupied by an AHL analog and therefore disturb AHL synthesis ( Chung et al, 2011 ). Another example is diketopiperazines that target CepI, an AHL synthase of B. cenocepacia , can interfere with the activity of signaling molecule synthases, rendering the bacteria unable to produce biofilms ( Buroni et al, 2018 ).…”
Section: The Mechanisms Of Qs Inhibiting Agents Suppressing Biofilm Fmentioning
confidence: 99%